Age-dependent Disturbances of Neuronal and Glial Protein Expression Profiles in Areas of Secondary Neurodegeneration Post-stroke. (21st November 2018) - Kluge, Murielle G.; Jones, Kimberley; Kooi Ong, Lin; Gowing, Emma K.; Nilsson, Michael; Clarkson, Andrew N.; Walker, Frederick R.
Highlights: Age exacerbates neurodegeneration after stroke in terms of synaptic protein expression. Age increases the aggregation and alters the accumulation profile of Amyloid β in areas of SND post-stroke. Microglia and astrocyte protein expression profiles in post-stroke SND remain relatively unaffected by age. Abstract: Despite the fact that approximately 80% of strokes occur in those aged over 60 years, many pre-clinical stroke studies have been conducted in younger adult rodents, raising debate about translation and generalizability of these results. We were interested in potential age differences in stroke-induced secondary neurodegeneration (SND). SND involves the death of neurons in areas remote from, but connected to, the site of infarction, as well as glial disturbances. Here we investigated potential differences in key parameters of SND in the thalamus, a major site of post-stroke SND. Protein expression profiles in young adult (2–4 months) and aged (22–23 months) mice were analyzed 28 days after a cortical stroke. Our results show that age reduced the expression of synaptic markers (PSD 95, Synapsin1) and increased Amyloid β oligomer accumulation after stroke. Protein expression of several markers of glial activity remained relatively stable across age groups post-stroke. We have identified that age exacerbates the severity of SND after stroke. Our results, however, do not support a view that microglia or astrocytes are the main contributors to the enhanced severity of SND in aged mice.